Driven by Purpose: How Protean Career Orientation Shapes Academic Success through Career Milestones - Alshaikhmubarak, Abdulrahman; Aljabr, Njod (Journal of Posthumanism, 2025)
This study explores how having a protean career orientation—where individuals take charge of their own career paths and focus on personal growth—affects the performance of university academics. It also looks at how career success might explain this relationship. Using data from 586 faculty members at universities in Saudi Arabia, the study applied quantitative methods and structural equation modeling to test the proposed relationships. The results showed that protean career orientation has a strong positive effect on career satisfaction, promotion, and salary increases. However, it did not directly improve academic performance. Among the possible mediators, only promotion played a significant role in linking protean career orientation to academic performance. Career satisfaction and salary increase did not have a meaningful effect in this link. These findings suggest that academics who actively manage their careers are more likely to succeed professionally, especially in terms of promotions, which in turn can lead to better performance. The study offers insights into how supporting self-driven career development can benefit both individual academics and academic institutions.